2015
DOI: 10.1016/j.cegh.2014.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of under nutrition in under-five tribal children of Melghat: A community based cross sectional study in Central India

Abstract: UnderweightWasting SAM a b s t r a c t Objective: Under nutrition has chronically remained a major public health problem among tribal children population in India. The present study aimed to estimate the prevalence of various forms of under nutrition in 'under five' children in Melghat e a difficult to reach, hilly, forest area of Maharashtra in Central India using different standards.Methods: A community based cross-sectional study was conducted in Dharni & Chikhaldara blocks in tribal area of Melghat over a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…Child malnutrition rates are also significantly higher and poverty more common for tribal populations compared with other populations3. In a cross-sectional study conducted in 2015, three-fourths (76.6%) of the 2926 under-5 children surveyed among tribal district of Melghat in Maharashtra, India, were found to be severely or moderately undernourished11. The situation of undernutrition is extremely worrisome in most tribal areas12.…”
Section: Why Tribal Health Mattersmentioning
confidence: 99%
“…Child malnutrition rates are also significantly higher and poverty more common for tribal populations compared with other populations3. In a cross-sectional study conducted in 2015, three-fourths (76.6%) of the 2926 under-5 children surveyed among tribal district of Melghat in Maharashtra, India, were found to be severely or moderately undernourished11. The situation of undernutrition is extremely worrisome in most tribal areas12.…”
Section: Why Tribal Health Mattersmentioning
confidence: 99%
“…1,5 Acute malnutrition is attributable to 14.6% of all child deaths having 8 times more fatality rate among malnourished children than normal children. [6][7][8][9] The prevalence of chronic malnutrition in India is among the highest in the world, and is nearly double than that of Sub-Saharan Africa, with dire consequences of mortality, morbidity, educability, and productivity. [9][10][11] Prevalence of malnutrition is much higher in tribal India.…”
Section: Introductionmentioning
confidence: 99%
“…Our study revealed prevalence of severe malnutrition (SAM -7.1%, SUW -18.7%, and severe stunting -34.4%) in U5 children of Melghat. 8 Prevalence of moderate and severe malnutrition (脌2SD WHO) in tribal Melghat is as wasting in 26%, underweight in 58.4%, and stunting in 66.1%. 8 These levels are considered very high, above the 'WHO Trigger Levels', indicating a need for public health interventions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations